Four‐Membered Heterometallacyclic d0 and d1 Complexes of Group 4 Metallocenes with Amidato Ligands. Issue 25 (23rd May 2014) - Haehnel, Martin; Priebe, Jacqueline B.; Yim, Jacky C.‐H.; Spannenberg, Anke; Brückner, Angelika; Schafer, Laurel L.; Rosenthal, Uwe
Abstract: A study of the coordination chemistry of different amidato ligands [(R)NC(Ph)O] (R=Ph, 2, 6‐diisopropylphenyl (Dipp)) at Group 4 metallocenes is presented. The heterometallacyclic complexes [Cp2 M(Cl){κ 2 ‐ N, O ‐(R)NC(Ph)O}] M=Zr, R=Dipp (1 a ), Ph (1 b ); M=Hf, R=Ph (2 )) were synthesized by reaction of [Cp2 MCl2 ] with the corresponding deprotonated amides. Complex 1 a was also prepared by direct deprotonation of the amide with Schwartz reagent [Cp2 Zr(H)Cl]. Salt metathesis reaction of [Cp2 Zr(H)Cl] with deprotonated amide [(Dipp)NC(Ph)O] gave the zirconocene hydrido complex [Cp2 M(H){κ 2 ‐ N, O ‐(Dipp)NC(Ph)O}] (3 ). Reaction of 1 a with Mg did not result in the desired Zr(III) complex but in formation of Mg complex [(py)3 Mg(Cl) {κ 2 ‐ N, O ‐(Dipp)NC(Ph)O}] (4 ; py=pyridine). The paramagnetic complexes [Cp′2 Ti{κ 2 ‐ N, O ‐(R)NC(Ph)O}] (Cp′=Cp, R=Ph (7 a ); Cp′=Cp, R=Dipp (7 b ); Cp′=Cp*, R=Ph (8 )) were prepared by the reaction of the known titanocene alkyne complexes [Cp2 ′Ti(η 2 ‐Me3 SiC2 SiMe3 )] (Cp′=Cp (5 ), Cp′=Cp* (6 )) with the corresponding amides. Complexes 1 a, 2, 3, 4, 7 a, 7 b, and 8 were characterized by X‐ray crystallography. The structure and bonding of complexes 7 a and 8 were also characterized by EPR spectroscopy. Abstract : Coordination chemistry : Heterometallacyclic complexes of the type [Cp2 M(L){κ 2 ‐ N, O ‐(Dipp)NC(Ph)O}] (M=Ti, no L; M=Zr, L=Cl; Dipp=2, 6‐diisopropylphenyl; see scheme) can be prepared by a hydrogen‐evolution reaction from either [Cp2 Ti(η 2 ‐Me3 SiC2 SiMe3 )] or Schwartz reagent [Cp2 Zr(H)Cl], giving the corresponding metallacycles in very high yields. EPR measurements revealed the stabilizing effect of the amidate ligand for paramagnetic d 1 Ti III complexes.